Antibodies in cerebral cavernous malformations react with cytoskeleton autoantigens in the lesional milieu. Issue 113 (September 2020) - Zhang, Dongdong; Kinloch, Andrew J.; Srinath, Abhinav; Shenkar, Robert; Girard, Romuald; Lightle, Rhonda; Moore, Thomas; Koskimäki, Janne; Mohsin, Azam; Carrión-Penagos, Julián; Romanos, Sharbel; Shen, Le; et al.
Abstract: Previous studies have reported robust inflammatory cell infiltration, synthesis of IgG, B-cell clonal expansion, deposition of immune complexes and complement within cerebral cavernous malformation (CCM) lesions. B-cell depletion has also been shown to reduce the maturation of CCM in murine models. We hypothesize that antigen(s) within the lesional milieu perpetuate the pathogenetic immune responses in CCMs. This study aims to identify those putative antigen(s) using monoclonal antibodies (mAbs) derived from plasma cells found in surgically removed human CCM lesions. We produced human mAbs from laser capture micro-dissected plasma cells from four CCM patients, and also germline-reverted versions. CCM mAbs were assayed using immunofluorescence on central nervous system (CNS) tissues and immunocytochemistry on human primary cell lines. Antigen characterization was performed using a combination of confocal microscopy, immunoprecipitation and mass spectrometry. Affinity was determined by enzyme-linked immunosorbent assay, and specificity by multi-color confocal microscopy and quantitative co-localization. CCM mAbs bound CNS tissue, especially endothelial cells and astrocytes. Non-muscle myosin heavy chain IIA (NMMHCIIA), vimentin and tubulin are three cytoskeleton proteins that were commonly targeted. Selection of cytoskeleton proteins by plasma cells was supported by a high frequency of immunoglobulin variable region somatic hypermutations, high affinity and selectivity of mAbs in their affinity matured forms, and profoundly reduced affinity and selectivity in the germline reverted forms. Antibodies produced by plasma cells in CCM lesions commonly target cytoplasmic and cytoskeletal autoantigens including NMMHCIIA, vimentin and tubulin that are abundant in endothelial cells and astrocytes. Binding to, and selection on autoantigen(s) in the lesional milieu likely perpetuates the pathogenetic immune response in CCMs. Blocking this in situ autoimmune response may yield a novel treatment for CCM. Highlights: Antibodies produced by plasma cells in CCM lesions are primary bound to endothelial cells and astrocytes. CCM-related autoantibodies target mainly cytoskeletal autoantigens including NMMHCIIA, vimentin and tubulin. An autoimmune reaction within lesions suggests novel mechanisms related to physiopathogenesis of CCMs. Characterizing relationships between autoimmunity and clinical outcomes may open novel treatments for CCM disease.